Guidance for emergency medicine pharmacists to improve care for people with opioid use disorder. Issue 2 (29th November 2021) - Kelsch, Jordan R.; Bailey, Abby M.; Baum, Regan A.; Metts, Elise L.; Weant, Kyle A.
Abstract: The Emergency Medicine Pharmacist (EMP) is uniquely trained to play a vital role in the management of patients who use opioids and patients with opioid use disorder (OUD). The emergency department (ED) is at the forefront of the opioid epidemic, as it serves as a primary place of treatment for patients experiencing opioid overdose, opioid withdrawal, and other complications related to opioid use. Given the size of the epidemic and the limited availability of treatment facilities and providers, the ED provides an opportunity to meet the needs of this patient population. Emergency Medicine Pharmacists can take an active role in the expansion of access to treatment of OUD, overdose education and prevention, and harm‐reduction interventions. Emergency Medicine Pharmacists have the ability to identify patients who would benefit from therapy, initiate appropriate treatment, provide patient counseling and education, lead the development of institution‐specific protocols and clinical decision tools, and assist in the evaluation of current strategies at their institution. Emergency Medicine Pharmacists' knowledge and understanding of the pharmacology of the drugs used to treat OUD is unique and should be utilized to improve patient care for this population. Further, EMPs are poised to limit the emergence of OUD before it begins through the implementation of opioid stewardship activities both within the ED and upon discharge. This article seeks to review the ways in which EMPs can support efforts in the ED to improve the care of people with OUD.